Bone mineral density in nonsteroid treated early rheumatoid arthritis. Issue 10 (October 1994) - Shenstone, B D; Mahmoud, A; Woodward, R; Elvins, D; Palmer, R; Ring, F; Bhalla, A K
Abstract : OBJECTIVES--To determine whether significant reduction in bone mass is detectable in early disease in patients with rheumatoid arthritis (RA) and to examine the possible influences of disease activity and physical disability on bone mineral density (BMD) of the lumbar spine (LS) and femoral neck (FN). METHODS--LS and FN BMD values were measured and Z scores determined in a cross-sectional study of 104 patients with RA of less than five years duration. BMD values were also compared between a subgroup of 64 patients and a normal control group matched for age, sex, menopausal status and body mass. BMD values and Z scores were correlated with disease activity, measured by the Stoke Index, disability, measured by HAQ score, and disease duration. RESULTS--Premenopausal female patients with RA had significantly reduced mean FN Z scores (-0.62, 95% CI -0.30 to -0.94) which correlated with HAQ scores (Rs 0.358, p = 0.05) and age (Rs 0.397, p = 0.03). There were no significant changes of BMD in males or postmenopausal females. Disease duration and disease activity did not correlate with BMD changes. CONCLUSION--BMD is reduced in premenopausal female patients with early RA possibly related to the attainment of peak bone mass. No significant reduction of BMD was found in males or postmenopausal females with early disease. Physical disability but not disease activity appears to play a role in the reduction of FN bone mass.